2015
DOI: 10.2478/aut-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Japanese and Chinese Clothing Evaluations by Experts Taking into Account Marketability

Abstract: To better understand the reasons for the marketability of clothing now designed and sold in China and Japan, we asked Japanese and Chinese experts to evaluate Chinese and Japanese brands of clothing currently for sale in the Japanese market. The marketability of the Chinese apparel items in the Japanese market was evaluated by the Japanese experts. Five Japanese jackets were purchased from a department store in Tokyo, and ten items of Chinese clothing were purchased from a department store in Beijing. Five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…However, the widespread adoption of a low-priced leadership strategy by exporting companies led consumers to associate Chinese products with low quality (Karanfil 2015 ; Zhang and Su 2009 ). Researchers have presented the existing perception by comparing Chinese goods to both domestic and foreign goods in several countries (Franco and Roach 2018 ; Khan and Ahmed 2012 ; Kim et al 2015 ; Laforet and Chen 2012 ; Schniederjans et al 2004 ; Srivastava 2015 ; Watung 2014 ). Over time, consumers generalized this perception about all Chinese products, including those of higher quality (Barney and Zhang 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the widespread adoption of a low-priced leadership strategy by exporting companies led consumers to associate Chinese products with low quality (Karanfil 2015 ; Zhang and Su 2009 ). Researchers have presented the existing perception by comparing Chinese goods to both domestic and foreign goods in several countries (Franco and Roach 2018 ; Khan and Ahmed 2012 ; Kim et al 2015 ; Laforet and Chen 2012 ; Schniederjans et al 2004 ; Srivastava 2015 ; Watung 2014 ). Over time, consumers generalized this perception about all Chinese products, including those of higher quality (Barney and Zhang 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese manufacturers have recently begun producing their own garment brands, including high-end garments, to sell in China. Kim et al (2015) evaluated garments to investigate the differences in garment marketability between Japanese and Chinese garments and found that garment evaluation criteria differed depending on countries. The results showed that although the sewing quality in some of these garments was inadequate for the Japanese market at that time, some garments were evaluated as being marketable in the Japanese market.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on those conceptions, fashion and tastes differ around the world (Yao et al , 2016). The same product can be seen differently from one country to another (Kim et al , 2014a, b; Kim, Nozawa and Takatera, 2015; Kim, Takatera, Zhu and Otani, 2015). Pattern making methods also differs depending on the country (Fujii et al , 2016).…”
Section: Introductionmentioning
confidence: 99%